(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Digital image forgery has become a significant concern due to the ease of manipulating anddistributing digital media. Content-preserving forgeries are particularly challenging to detect, as theymaintain the visual integrity of the original image while altering its content. In this research paper, wepropose a novel image forgery detection method that combines Support Vector Machines (SVM),Convolutional Neural Networks (CNN), and ensemble classifiers to enhance the accuracy and reliabilityof forgery detection.